C. B. Strike. Lethal white [videorecording (DVD)] - Galbraith, Robert; Johnston, Adrian; Naumiuk, Tomasz, 1981-; Blood, Nick, 1982-; Cole, Christina, 1982-; Coomber, Saffron, 1994-; Greenlees, Jack; Gumede, Natalie; Logan, Kerr; Long, Adam (Actor); Quinn, Joseph (Actor); Winkleman, Sophie, 1980-; et al. (Warner Home Video, 2021)
Season three of this dark, gritty crime drama follows two concurrent mysteries: one the case of a man suffering from psychosis, desperate to find answers about a girl he saw strangled years ago. The other, the case of a government minister blackmailed by the same man's brother. However, the mystery of how these two cases connect is not the only source of driving tension. Fans of the series want to know if Cormoran and his assistant Robin end up together, a question that Lethal White builds up through Robin's flailing new marriage and Cormoran's own messy love life.